Effectiveness of Pre-Operative Subcutaneous Infiltration of Ketamine for Post-Operative Analgesia and Haemodynamic Attenuation (KYAMC Journal, 2021)
Background: Ketamine is a noncompetitive antagonist of N-methyl-D-aspartate (NMDA) receptor which plays an important role in pain modulation. It decreases acute postoperative pain by inhibiting C fiber activity.Objective: Purpose of this study was to evaluate the effectiveness of preoperative subcutaneous infiltration of ketamine for postoperative analgesia and haemodynamic attenuation.Materials and Methods: This Randomized controlled trial study was conducted among the patients with ASA (Ameracin Society of Anaesthesiologist) grade I & II, planned for major abdominal surgery with upper midline incision. Total 60 patients were selected and allocated into two groups, 30 in each- group A & B. Group A - Patients received subcuteneous wound infiltration with ketamine. Group B - Patients given subcuteneous wound infiltration with bupivacaine. Then haemodynamic status and patient outcome was assessed at different point of time.Results: There was no significant difference between groups in respect of demographic and ASA status. Mean age was found to 38.7±8.53 years. In Group A, 63.3% were ASA I and 36.7% were ASA II. In Group B, 60% were ASA I and 40% were ASA II. It has become evident that satisfactory analgesia can be acheived by subcuteneous wound infiltration with ketamine (in Group-A).The Mean verbal pain score was 5.2±0.47 and 7.4±0.68 in group A & group B respectively. The difference was statistically significant (p